2016
DOI: 10.1007/s13317-016-0077-y
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold videocapillaroscopy and serum VEGF levels in scleroderma are associated with internal organ involvement

Abstract: PurposeNailfold videocapillaroscopy (NVC) identifies the microvascular hallmarks of systemic sclerosis (SSc) and vascular endothelial growth factor (VEGF) and may play a pivotal role in the associated vasculopathy. The aim of the present study was to compare NVC alterations with clinical subsets, internal organ involvement, and serum VEGF levels in a cohort of selected SSc cases.MethodsWe studied 44 patients with SSc who were evaluated within 3 months from enrollment by NVC, skin score, severity index, pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 31 publications
0
28
1
1
Order By: Relevance
“…A 20-year prospective study following the disease course of patients with RP, noted transition on nailfold capillaroscopy (NC) from giant capillaries to capillary loss occurring in close temporal relationship to the emergence of clinical features that led to a diagnosis of definite SSc (usually defined by the emergence of cutaneous fibrosis) [20]. A number of studies have also identified a positive and progressive association between the severity of microangiopathy on NC and the extent of skin fibrosis [21][22][23][24][25]. Indeed, 'early' changes are more frequently identified in limited cutaneous SSc (lcSSc) [23,26] whereas 'late' changes are more prevalent in diffuse cutaneous SSc (dcSSc) [19,25].…”
Section: Vasculopathy In Systemic Sclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…A 20-year prospective study following the disease course of patients with RP, noted transition on nailfold capillaroscopy (NC) from giant capillaries to capillary loss occurring in close temporal relationship to the emergence of clinical features that led to a diagnosis of definite SSc (usually defined by the emergence of cutaneous fibrosis) [20]. A number of studies have also identified a positive and progressive association between the severity of microangiopathy on NC and the extent of skin fibrosis [21][22][23][24][25]. Indeed, 'early' changes are more frequently identified in limited cutaneous SSc (lcSSc) [23,26] whereas 'late' changes are more prevalent in diffuse cutaneous SSc (dcSSc) [19,25].…”
Section: Vasculopathy In Systemic Sclerosismentioning
confidence: 99%
“…In view of the characteristic microvascular manifestations of SSc, VEGF-A pathways have attracted interest as potentially important drivers of disease pathogenesis. In view of the pronounced capillary drop out found in SSc, the authors of early studies were surprised to identify high levels of circulating serum VEGF-A in both early [9] and established SSc [22,54], although serum VEGF-A was noted to be comparatively lower in SSc patients with DU [9,55]. VEGF associations with systemic organ manifestations of SSc have been less extensively studied and are notably varied.…”
Section: The Potential Role Of Vegf In Ssc Related Vasculopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Аналогичная взаимосвязь -обратная корреляция между концентрацией VEGF в крови и ДЛСО у больных ССД -получена и в работе M. De Santis и соавт. [27].…”
Section: обсуждение и заключениеunclassified
“…However, paradoxically a deficit of angiogenesis in the skin of these patients has been reported with development of avascular areas in the skin and in the internal organs, leading to digital ulcers, skin and organ fibrosis. 1 The detection of vascular endothelial growth factor (VEGF) in the circulation of SSc patients has given conflicting results, while in some studies VEGF and other pro-angiogenic mediators, such as fibroblast growth factor (FGF)-2 and interleukin (IL)-8, have been shown to be up-regulated; [2][3][4] in others the levels of VEGF were similar to those of healthy controls. 5 Among the antiangiogenic mediators, endostatin (ES), by inhibiting VEGF, is one of the main anti-angiogenic molecules in physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%